Female educational supervisors and problems in the educational field - Al-Tarisi, Hessa Jahz Zaben; Al-Abiky, Waleed Ibrahim Ali (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to identify the educational field problems faced by female supervisors. To achieve the study’s goal, the researcher used a qualitative approach based on the basic explanatory design. A purposive sample of 25 female educational supervisors from the Al-Rass region, under the Department of Education in Al-Qassim, was selected. The research tool (focus groups through interviews) was applied to various specializations: (Arabic Language, Islamic Studies, Mathematics, English Language, and Supervision). Data were analyzed using two strategies: line-by-line analysis, and the case-by-case comparison strategy. The researcher used the qualitative analysis program (MAXQDA) as an auxiliary tool for analyzing qualitative data. The results showed that the participants agreed that the role of educational supervisors was moderate in addressing educational field problems, with excellence in developing cognitive aspects, despite a lack of support in the therapeutic and procedural areas. The results emphasized the importance of continuous training programs to develop teachers’ skills and overcome challenges in the educational field. The significance of therapeutic approaches such as self-directed professional learning, reflective practices, and teacher pairing to improve performance and effectively address obstacles was also highlighted. Based on the results, the study recommended emphasizing this modern approach in educational supervision by holding in-service training courses for educational supervisors and equipping them with the skills to use developmental educational supervision patterns through in-service training courses for female educational supervisors.
Keywords: challenges in the educational field; Educational supervisors